Light-emitting diodes in dermatology: stimulation of wound healing - Fryc, Justyna; Fryc, Irena (Dermatology Review/Przegląd Dermatologiczny, 2016)
Low-level light therapy (LLLT), which is sometimes included in phototherapy, is an effective therapeutic strategy to improve wound healing and reduce pain, inflammation and swelling. Nowadays, new sources of light, such as light-emitting diodes (LEDs) with a broad range of wavelengths, are widely available. The biological effects promoted by LEDs are dependent on irradiation parameters, mainly wavelength and dose. This review article focuses on recent clinical trials using light-emitting diode low-level light therapy (LED-LLLT) for enhancing wound healing. In this article, we also cover the mechanisms of action of LLLT on cells and tissues and highlight the importance of defining optimum LLLT parameters for stimulation of wound healing.